1997
DOI: 10.3354/meps146073
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effects of the dinoflagellate Heterocapsa circularisquama on clearance rate of the blue mussel Mytilus galloprovincialis

Abstract: The effects of Heterocapsa circularisquama (Peridiniales, Dinophyceae) on the clearance rate of blue mussel Mytilus galloprovjncialis were studied in the laboratory to clarify the mechanism involved in the toxic effects of dinoflagellates on bivalve mollusks The clearance rate of blue mussels was s~gnificantly reduced when exposed to H. circularisquama, even at a low dinoflagellate cell density (50 cells ml-'). Mussels also showed extreme retraction of the mantle edge and no production of feces or pseudofeces.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
49
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 23 publications
2
49
0
1
Order By: Relevance
“…!C were c n~~n t~r l individually (= 245 P. kofoidii pseudocolonies) under blue light excitation. The P. kofoidii cells were immobilized using nickel chloride treatment at a final concentration of ca 40 pg 1-' (Matsuyama et al 1997). Plankton cell size and volume were determined on the immobilized cells.…”
mentioning
confidence: 99%
“…!C were c n~~n t~r l individually (= 245 P. kofoidii pseudocolonies) under blue light excitation. The P. kofoidii cells were immobilized using nickel chloride treatment at a final concentration of ca 40 pg 1-' (Matsuyama et al 1997). Plankton cell size and volume were determined on the immobilized cells.…”
mentioning
confidence: 99%
“…5) In contrast to the severe shellfish toxicity of H. circularisquama, no significant toxic effects of Heterocapsa triquetra, which is known as a morphologically analogous species to H. circularisquama and has worldwide distribution, on bivalves and other marine organisms have so far been observed. 6) Matsuyama et al have shown several lines of evidence supporting the idea that unstable toxic substances located on the surface of H. circularisquama cells may be responsible for its toxicity to bivalves. 6) Since such other harmful dinoflagellates as Gyrodinium aureolum are known to kill shellfish, finfish and crustacean species, the shellfish-specific toxicity of H. circularisquama is a unique characteristic of this alga.…”
mentioning
confidence: 89%
“…6) Matsuyama et al have shown several lines of evidence supporting the idea that unstable toxic substances located on the surface of H. circularisquama cells may be responsible for its toxicity to bivalves. 6) Since such other harmful dinoflagellates as Gyrodinium aureolum are known to kill shellfish, finfish and crustacean species, the shellfish-specific toxicity of H. circularisquama is a unique characteristic of this alga. 7) We have found in our previous studies that H. circularisquama showed potent hemolysis toward rabbit erythrocytes through direct cell-to-cell contact, whereas H. triquetra showed no significant hemolytic activity.…”
mentioning
confidence: 89%
“…This notion may be supported by thê nding that shellˆsh toxicity disappeared after the treatment with detergent without aŠecting the integrity of ‰agellate cells. 8,13) Since hemolytic activity in the culture supernatant decreased rapidly, such hemolytic toxin may be unstable in the medium after once released from the cells in which such toxin may be continuously produced during cell growth (data not shown).…”
Section: Days After Exposure Mortality (Z)mentioning
confidence: 99%
“…6) Recently, it has been reported that pearl oysters exposed to H. circularisquama (5,000 to 10,000 of cells W ml) showed vigorous clapping and shrinkage of their mantle edges and gills, and about 50z of the pearl oysters subsequently underwent cardiac arrest and eventually died after 48 h. 7) Regarding the mechanism of shellˆsh toxicity of this dino‰agellate, Matsuyama et al have shown several lines of evidence supporting the idea that unstable toxic substances located on the surface of H. circularisquama cells may be responsible for the toxicity to bivalves. 8) Furthermore, Matsuyama has observed that an in‰ux of Ca 2+ was induced in trochophore larva of the short-necked clams (Ruditapes philippinarum) after exposure to H. circularisquama.…”
mentioning
confidence: 99%